2016
DOI: 10.1208/s12249-016-0547-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Calibration-Minimum Method for Prediction of Mole Fraction in Non-Ideal Mixture

Abstract: This article proposes a novel concentration prediction model that requires little training data and is useful for rapid process understanding. Process analytical technology is currently popular, especially in the pharmaceutical industry, for enhancement of process understanding and process control. A calibration-free method, iterative optimization technology (IOT), was proposed to predict pure component concentrations, because calibration methods such as partial least squares, require a large number of trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Funatsu et al identified this weakness in the method and proposed two ways to mitigate it. One is to limit the region(s) of the spectra to be included into the analysis using of a genetic algorithm for variable selection, and the other is the modification of the inner relationship in BLL adding a nonlinear term. , The latter extension requires the estimation of a nonlinear pure spectrum and an exponent for the molar fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Funatsu et al identified this weakness in the method and proposed two ways to mitigate it. One is to limit the region(s) of the spectra to be included into the analysis using of a genetic algorithm for variable selection, and the other is the modification of the inner relationship in BLL adding a nonlinear term. , The latter extension requires the estimation of a nonlinear pure spectrum and an exponent for the molar fractions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach implies the additional estimation of the nonlinear spectral signatures ( s nonlinear,n ) and the order ( p n ) of the nonlinear component per ingredient. None of these proposals addresses the fact that the estimate of r n is a molar fraction bolddfalse^new=n()rnsn+rnpnsitalicnonlinear,n …”
Section: Introductionmentioning
confidence: 99%
“…However, the predictive accuracy of nonlinear IOT largely depends on training samples and the wavelength regions used. IOT with virtual molecular interaction spectra (IOT-VIS) has been developed [14]. It can express spectral change as nonlinear terms and requires few training samples.…”
Section: Introductionmentioning
confidence: 99%